2001
DOI: 10.1007/s00134-001-1129-x
|View full text |Cite
|
Sign up to set email alerts
|

Should we confirm our clinical diagnostic certainty by autopsies?

Abstract: Autopsies are performed more often in younger patients without chronic disease and in patients with a low clinical diagnostic certainty. No level of clinical diagnostic certainty could predict the pathological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 0 publications
1
41
3
1
Order By: Relevance
“…Parents of infants with uncertain antemortem diagnoses are potentially more likely to grant permission for autopsy, which could cause a selection bias. Therefore, the number of additional findings in the present study might be higher than the number of findings in all deceased NICU patients [18, 19]. However, minor Goldman findings were present even after a more prolonged NICU stay, suggesting that these additional findings could have been found in deceased patients without permission for autopsy as well.…”
Section: Discussioncontrasting
confidence: 45%
“…Parents of infants with uncertain antemortem diagnoses are potentially more likely to grant permission for autopsy, which could cause a selection bias. Therefore, the number of additional findings in the present study might be higher than the number of findings in all deceased NICU patients [18, 19]. However, minor Goldman findings were present even after a more prolonged NICU stay, suggesting that these additional findings could have been found in deceased patients without permission for autopsy as well.…”
Section: Discussioncontrasting
confidence: 45%
“…Podbreg ar et al [11] 2001 126 52 10.5 In our study class I discrepancies were found in 31 cases of total 63 discrepant cases (49.21%), which is concordant with a MICU study of Tai et al [8] who reported 44% (8 of 18) of class I errors.…”
Section: Discussionsupporting
confidence: 90%
“…This observation has also been made by other investigators [2,3,6] and emphasises the difficulty of diagnosing unexpected or new pathogens in patients with already manifest infections. For example, the number of Legionella infections in Finland is very low, 6-12 cases annually, as is the incidence of tuber- [7].…”
Section: Discussionmentioning
confidence: 74%